Audit Delay pada IDX-30: Peran Ukuran KAP, Ukuran Perusahaan, dan Umur Perusahaan - Sovi Mahalaxmi Dewi; Warsani Purnama Sari; Yusnaini Yusnaini; Wardhani Indah Sari; Ahmad Prayudi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to investigate the impact of public accounting firm size, company size, and company age on audit delays in IDX-30 companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This study uses a quantitative research design with an associative approach. The type of data used is quantitative data in the form of audited annual financial reports from 2021 to 2024. The population in this study consists of 30 companies classified as IDX-30. The research sample uses Purposive sampling by applying the criteria that the company must be consistently listed on the IDX-30 from 2021 to 2024. The sample consists of 17 companies with an observation period of four years, resulting in a total of 68 samples analysed. The data source is secondary data. The data collection technique is documentation. The independent variables in this study include the size of the public accounting firm (X1), company size (X2), and company age (X3), while the dependent variable is audit delay. The analysis method used was logistic regression. The results show that, partially, company size has a positive and significant effect on audit delay. The size of the public accounting firm and the age of the company do not affect audit delay. Simultaneously, the size of the public accounting firm, company size, and company age show a significant effect on audit delay in IDX-30 companies listed on the IDX during the research period